The diagnosis of autism and autism spectrum disorder in low- and middle-income countries: Experience from Jamaica. (July 2017) - Samms-Vaughan, Maureen; Rahbar, Mohammad H; Dickerson, Aisha S; Loveland, Katherine A; Hessabi, Manouchehr; Pearson, Deborah A; Bressler, Jan; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Coore-Desai, Charlene; Reece, Jody; Boerwinkle, Eric
The administration requirements of the Autism Diagnostic Observation Schedule and the Autism Diagnostic Interview–Revised, widely used in high-income countries, make them less feasible for diagnosis of autism spectrum disorder in low- and middle-income countries. The flexible administration requirements of the Childhood Autism Rating Scale have resulted in its use in both high-income countries and low- and middle-income countries. This study examines the agreement between assessments using the Childhood Autism Rating Scale with those using the Autism Diagnostic Observation Schedule or Autism Diagnostic Observation Schedule, Second Edition and Autism Diagnostic Interview–Revised in Jamaica. Children aged 2–8 years (n = 149) diagnosed with autism by an experienced clinician using the Childhood Autism Rating Scale were re-evaluated using the Autism Diagnostic Observation Schedule and Autism Diagnostic Interview–Revised. The proportion diagnosed with autism spectrum disorder using the Autism Diagnostic Observation Schedule, Autism Diagnostic Observation Schedule, Second Edition, and Autism Diagnostic Interview–Revised was determined and mean domain scores compared using analysis of variance (ANOVA). The mean age was 64.4 (standard deviation = 21.6) months; the male:female ratio was 6:1. The diagnostic agreement of the Childhood Autism Rating Scale with the Autism Diagnostic Observation Schedule and Autism Diagnostic Observation Schedule, Second Edition was 100.0% and 98.0%, respectively. Agreement with the Autism Diagnostic Interview–Revised was 94.6%. Domain scores were highest for children with more severe symptoms (p < 0.01). Despite a high level of agreement of the Childhood Autism Rating Scale with the Autism Diagnostic Observation Schedule, Autism Diagnostic Observation Schedule, Second Edition, and Autism Diagnostic Interview–Revised, the Childhood Autism Rating Scale should be evaluated further with a broader range of autism spectrum disorder symptomatology, and by clinicians with varying experience before recommendation for use in low- and middle-income countries.